Conceptual Framework For Ensuring Economic Security Of Territorial Communities In Ukraine - MOSHCHANETS, Andrii (University Scientific Notes, 2024)
The article systematises scientific approaches to the definition of «security». The author emphasises the lack of a unified approach to understanding the content of the concept of «economic security of the state» and outlines the main scientific views on its interpretation. The peculiarities of the legislative use of the category «economic security» are analysed. The main characteristics and functional significance of the economic security of the state are outlined, and its fundamental role as a material basis for determining the real possibilities of ensuring other types of security is emphasised. It is noted that economic security is a multi-level system, covering not only the national level but also integrating regional and local components. A number of approaches to determining the levels of the hierarchy of the main types of economic security are presented, and it is suggested that the economic security of a territorial community should be considered as a separate level. It is proved that the state’s economic security begins with ensuring the economic security of the territorial communities. The study has established that the state’s economic security system is a complex set of interrelated elements, where each territorial community acts as a basic structural unit on the basis of which conditions are created to ensure the stable functioning of the national economy. It is emphasised that ensuring the economic security of a territorial community differs significantly from similar processes at the level of the state, region, or individual enterprise. The purpose and functions of territorial communities are clarified. It emphasises that an important prerequisite for ensuring the vital activity of a given territorial community and the effective performance of its functions is to ensure an adequate level of economic security. It is emphasised that an important prerequisite for ensuring the vital activity of a given territorial community and the effective performance of its functions is to ensure an adequate level of economic security. The key characteristics of economic security at the local level are highlighted. Threats are outlined and a territorial community’s economic security principles are defined. A personal approach to the definition of the concept of «economic security of a territorial community» is proposed.